Promosi Kesehatan Menjaga Kesehatan Ibu Hamil Melalui Upaya Konsumsi Vitamin Yang Tepat - Amanda, Dita; Kustriyani, Anung; Lestari, Ima Fitria; Wiarsini, Ni Kadek Mei; Maulidia (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2025)
Malnutrition are causes of stunting. Even though the number of stunting in Indonesia has decreased, efforts are still needed to increase public awareness, especially pregnant women. This is done so that babies born can avoid stunting. The aim of this community service activity is to provide information regarding the correct consumption of vitamins during pregnancy as an effort to prevent stunting. The methods used are video screening, counseling and providing health promotion media in the form of paper fans. Pregnant women also do pre-test and post-test questions. This community service activity was attended by 10 pregnant women from Posbindu Kemiren Village. The result of community service activities is that pregnant women receive information regarding the types of vitamins consumed during pregnancy and vitamin deficiencies in pregnant women. There was an increase in pregnant women who answered all post test questions correctly (10 respondents) compared to the pre test (6 respondents).